Motivasi Berprestasi sebagai Tanggung Jawab Guru dan Orang Tua terhadap Peserta Didik di Era 4.0 dan Relevansinya dalam Pendidikan Agama Kristen - Nemiarce Veblita Noti; Harun Y. Natonis (Lembaga Pengembangan Kinerja Dosen, 2025)
Achievement Motivation as the Responsibility of Teachers and Parents Towards Students in the 4.0 Era and Its Relevance in Christian Religious Education. The background of writing this article is to understand the motivation of students' learning achievement in the 4.0 era. The purpose of this study is to improve students' learning achievement, one of the determining factors of success is learning motivation. Motivation plays an important role in encouraging students to study diligently, tenaciously and with full concentration so that learning achievement can be optimal. The research method used in this study is qualitative research through literature study. The results are that learning motivation consists of intrinsic and extrinsic motivation which is influenced by various factors such as ideals, abilities, physical and psychological conditions of students, and the surrounding environment. Teachers and parents have an important role in providing achievement motivation through proper guidance, support, and supervision. In the era of the Industrial Revolution 4.0, the challenges of learning motivation are increasingly complex because it facilitates access to technology that can distract students. Therefore, the role of Christian religious education is very important in shaping the character and spiritual values ​​of students so that they are able to face technological challenges wisely, maintain face-to-face relationships, and foster strong learning motivation.